The life and death of dramatic character in the Romantic period, 1779-1839 - Dallas, H (2024)
In this thesis, I argue that a new model of dramatic character emerged in the Romantic period. Faced with the loss of David Garrick and his generation of actors who had revolutionised acting, ushering in the ‘natural style’ which tied the ‘life’ of the character onstage to the actor in a way not seen before, audiences were suddenly made aware that the characters that they loved were themselves ephemeral: audiences would never again see Garrick’s Hamlet, whom they had come to view as a character in his own right. This sense of loss, I suggest, brought about a shift in the relationship between theatre and memory, and instantiated what I describe as a ‘memorial model’ of dramatic character, in which the actor-as-character was memorialised, cited and represented in texts, images, and objects, as well as other performances, in order to archive the actor-as-character, and commit it to cultural memory, even in the face of the actor’s death. My thesis traces this Romantic evolution in dramatic character across emerging essay forms, including character criticism and critical prefaces; the various ways that the actor-as-character was preserved in and after a performance; the Romantic period’s famous ‘mental theatre’ of closet drama; and the textual, visual, and material ‘afterlives’ which kept the actor-as-character alive for generations who never got to see them onstage – including present-day theatre historians.